Correlation on the compliance control with the chronic complication among diabetes mellitus type 2 at the Janti Community Health Centre Malang - Hamarno, Rudi (University of Muhammadiyah Malang, 2016)
Pandemic of type 2 diabetes has become a serious threat to the human race in the world. In 2003. Based on data Persadia in East Java, the number of diabetics is estimated at 6% of the total population. The aim on study was to determine the corelation between the control of compliance with the occurrence of chronic’s complications in patients with type 2 diabetes in the Janti’s health center Malang. This study uses a case-control design with retrospective approach, enrolled in the Janti’s health center of Malang, from July 9-18, 2013, the respondent was obtained by purposive sampling about 30 respondents, comprising 15 respondents with type 2 diabetes without complications and 15 respondents with type 2 diabetes complications. The data was collected by using questionnaire and a food recall then we asses the respondent’s characteristics and respondents' compliance controls by interview. The data were process and analyzed by descriptive and statistical lambda tests. The results showed no complications of respondents 93% is obey to compliance control while chronic complications of respondents with 87% isn’t obey to compliance control. Lambda test results there is a relationship between the control of compliance with the occurrence of chronic complications proved to count p = 0.00 with a very strong correlation value of 0.88. Suggestion to the respondents can be more aware of and understand the importance of adhering to their health control as it helps keep blood sugar levels to keep it stable, so that the incidence of complications can be prevented.